VIDEOCONFERENCE AS A MEANS OF STUDENTS’ FOREIGN LANGUAGE TRAINING - Soter, Mariia (Mountain School of Ukrainian Carpaty, 2020)
The relevance of the implementation of videoconference in the educational process of higher education institutions has been emphasized. It has been noted that videoconference gives an opportunity to optimize both classroom and extracurricular students’ foreign language training. The aim of the article is to study the videoconference as a means of students’ foreign language training. To achieve the aim of scientific research, a set of methods has been used such as the method of analysis and systematization – to identify the problem at the present stage; the method of generalization – to represent the benefits of implementing videoconferencing in the educational process of higher education institutions. It has been emphasized that the advantages of using videoconferencing for students’ foreign language training of higher education institutions include: the creation of equal opportunities for access to interaction of students and lecturers (in particular, communicative interaction in the foreign language) regardless of their location at a suitable period of time for each participant of the conference; the implementation of student-centered learning and teaching, within which all efforts are aimed at providing each student individually and all together with the necessary information online; the availability of constant feedback among all subjects of the educational process (both through the dialogue among participants during the videoconference and with the help of engaging in chat during the conference); the expanding access to educational resources under the lecturer’s guidance and the exchange of information online; flexibility for the learner, due to the possibility of round-the-clock access to information in real time (anytime and anywhere); the visualization of the educational process online (see, hear the interlocutor, both the lecturer and all students, as well as the information offered by the lecturer, actively communicate; all these factors are important for foreign language training); simultaneous involvement of a significant number of participants from different regions of Ukraine and abroad.